Yield curve dynamics: Regional common factor model - Boril Šopov; Jakub Seidler (Charles University in Prague, Institute of Economic Studies (IES), 2010)
In this paper, we focus on thorough yield curve modelling. We build on extended classical Nelson-Siegel model, which we further develop to accommodate unobserved regional common factors. We centre our discussion on Central European currencies' yield curves: CZK, HUF, PLN and SKK. We propose a model to capture regional dynamics purely based on state space formulation. The contribution of this paper is twofold: we examine regional yield curve dynamics and we quantify regional interdependencies amongst considered currencies' yield curves. We conclude that the CZK yield curve possesses its own dynamics corresponding to country specific features, whereas other currencies' yield curves are strongly influenced by the regional level, the regional slope factor or both.
Keywords: C51; C53; G17; 330; dynamic factor model; kalman filter; Nelson-Siegel; state space; regional Yield Curve; principal component analysis; Zinsstruktur; Dynamisches Modell; Faktorenanalyse; Zustandsraummodell; Tschechische Republik; Slowakei; Polen; Ungarn